Development of incremental forming machine - Muhammad Safwan, Zakaria (2008)
This research was carried out to develop and analysis an incremental forming machine controlled by personal computer; numerical control (PC_NC). The application of this machine is to realize a small production lot with low cost. The process which runs without mould can be used to replace stamping applications which is very costly due to the mould application. Aim of this study is to analysis in contour geometry of forming relation to the tool path and relate with speed, torque and time of forming process. The analyses show the implication and justification for forming process. The experiments result determine the justification and FEM have been achieved with the purpose to compare between experimental and simulation. Experimental process and analysis have been use to determine the tool path in the design phase for continuous operation.